Stormwater management in urbanised areas in Poland. Analysis and assessment of current legislation - Marszelewski, Michał; Piasecki, Adam; Kaźmierczak, Bartosz (Bulletin of Geography. Socio-economic Series, 2024)
The issue of stormwater has an interdisciplinary dimension, but the work focuses on its legal and environmental aspects. The article analyses and evaluates Polish legal regulations in the field of stormwater management in urbanised areas. These regulations focus particularly on two different areas. The first is the discharge of stormwater into waters or the ground. The second concerns the reduction of natural land retention (the “rain tax”). These activities are always considered a form of water use that incurs a fee determined in accordance with the provisions of the Water Law. In both areas, both practice and legal doctrine raise interpretative doubts that stem from the applicable normative solutions. These doubts particularly concern the determination of entities obliged to take specific actions or the scope of application of the fee for reducing natural land retention. This, in turn, translates into difficulties in applying the law and non-uniformity of decisions made.